Development of the technology for the spectral noise control of the vibration conditions of offshore platforms - Aliev, Telman Abbas; Rzayeva, Narmin Eldar; Sattarova, Ulkar Eldar (Eastern-European Journal of Enterprise Technologies, 2018)
Because of the shortcomings in both control and diagnostic systems, the accident rate for offshore oil and gas extracting facilities remains unreasonably high. Accidents are often caused by the errors resulting from the application of traditional analytical technologies to noisy signals received from corresponding sensors. Our research shows that these technologies generally provide the informative attributes required to perform defect diagnostics only after the defect has already become strongly pronounced. For this reason, the results of monitoring of the beginning of transition of the platforms into an emergency state is sometimes delayed. Therefore, it is obvious that the creation of algorithms and other technologies to monitor the early onset and the development of cracks, wear and tear, corrosion, and other defects in offshore platforms is of enormous importance. Timely, preventive maintenance performed on these platforms can make it possible to avoid catastrophic accidents. According to the research we found that when defects arise in control objects, the noise ε2(t), correlated with the useful signal X(iΔt), appears in the signals g(iΔt) received from the corresponding sensors. For this case in the article the algorithms and technologies of spectral analysis of both vibration signal and its noise were proposed. By means of them it becomes possible to increase the reliability of monitoring the beginning of a latent period of transition to an emergency state of offshore platforms. This feature helps to improve the effectiveness of the control systems of offshore platforms.